Laser therapy is a safe and effective treatment for unwanted hair in adults undergoing male to female sex reassignment. (12th November 2020) - Vilenchik, V.; Thomas, K.; Baker, L.; Hitchens, E.; Keith, D.
Summary: Reduction in unwanted facial and body hair is an important goal in the process of sex reassignment. Laser treatment is a popular, well‐established safe and effective method of reducing unwanted hair growth. In the UK a limited number of laser treatment and electrolysis sessions are publically funded for people undergoing sex reassignment. To date, published evidence on efficacy and adverse effects (AEs) has focused on treatment of women and men not undergoing sex reassignment. In the current study, data were collected prospectively from 2015 to 2020 at a UK regional laser centre. Patients were included if they were transgender women aged > 16 years old and seeking laser treatment for unwanted hair at any body site. The study demonstrated significant reductions in hair growth and significant patient satisfaction, with no AEs. Laser treatment is a safe and effective method of managing unwanted hair growth in the transgender transfeminine population.